A case of efficacy of bendamustine in heavily pretreated multiple myeloma, refractory to pomalidomide. Issue 4 (8th March 2017) - Cerchione, Claudio; Nappi, Davide; Di Perna, Maria; Zacheo, Irene; Migliaccio, Ilaria; Salvatore, Dalila; Picardi, Marco; Pane, Fabrizio; Catalano, Lucio
Key Clinical Message: In this report, we would like to highlight the efficacy of bendamustine in a heavily pretreated patient, also refractory to pomalidomide. It is conceivable that different therapy combinations in heavily treated Multiple myeloma (MM) have to be explored, without "a priori" exclusion of ancient drugs, even after failure of the ultimate pharmacological options. Abstract : In this report, we would like to highlight the efficacy of bendamustine in a heavily pretreated patient, also refractory to pomalidomide. It is conceivable that different therapy combinations in heavily treated Multiple myeloma (MM) have to be explored, without "a priori" exclusion of ancient drugs, even after failure of the ultimate pharmacological options.